2016
DOI: 10.1039/c6ce00130k
|View full text |Cite
|
Sign up to set email alerts
|

The role of solvent in the self-assembly of m-aminobenzoic acid: a density functional theory and molecular dynamics study

Abstract: Please note that technical editing may introduce minor changes to the text and/or graphics, which may alter content. The journal's standard Terms & Conditions and the Ethical guidelines still apply. In no event shall the Royal Society of Chemistry be held responsible for any errors or omissions in this Accepted Manuscript or any consequences arising from the use of any information it contains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…Indeed this suggestion appears to be consistent with recent reports on the solvent induced aggregation of m-aminobenzoic acid [27] and imidazole [28] for which stacking interactions play a central role. Secondly, we can make an important link between these kinetic data and the world of crystal structure prediction.…”
supporting
confidence: 92%
“…Indeed this suggestion appears to be consistent with recent reports on the solvent induced aggregation of m-aminobenzoic acid [27] and imidazole [28] for which stacking interactions play a central role. Secondly, we can make an important link between these kinetic data and the world of crystal structure prediction.…”
supporting
confidence: 92%
“…Indeed it has even been suggested that solute can aggregate in undersaturated homogenous solutions 20, into the supersaturated region. Molecular modelling studies can provide insights into solution chemistry behaviour, for example indicating that the formation of H-bonding synthons, such as the classic OH…O carboxylic acid dimer, can template the nucleation of a crystalline form from specific solutions 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Dimers are the first aggregates that can form during the process of self-association and their structure often corresponds to the building unit of the crystal that grows from solution. [63][64][65][66] The chemical nature of the intermolecular interactions in the caffeine dimer (CAF) 2 can therefore be expected to control its aggregation. The rearrangement of the electronic charge of the face-to-face and face-to-back dimeric configurations found in the X-ray crystalline structure of caffeine 67,68 (Fig.…”
Section: Caffeine Dimersmentioning
confidence: 99%